Measuring the Sensitivity of the Composite Stock Price Index to Macroeconomic Shocks in Indonesia: Short- and Long-Term Analysis with the ARDL Model - Suprianto, Suprianto (Business Management, 2025)
This study aims to examine the sensitivity of Indonesia’s Composite Stock Price Index (CSPI) to macroeconomic shocks using the Autoregressive Distributed Lag (ARDL) model. By incorporating key macroeconomic variables such as inflation, interest rates, exchange rates, and industrial production, this research analyzes how short-term fluctuations and long-term equilibrium relationships influence stock market dynamics. The ARDL approach is employed due to its flexibility in estimating relationships among variables with mixed orders of integration. The empirical results reveal that macroeconomic shocks exert significant yet varying impacts on the CSPI in both the short and long run. In the short term, exchange rate volatility and interest rate adjustments show the strongest immediate influence on stock price movements. Conversely, in the long-term horizon, inflation and industrial production emerge as dominant determinants, indicating deeper structural linkages between macroeconomic fundamentals and market performance. The findings underscore the importance of stable macroeconomic conditions in sustaining stock market resilience. Furthermore, the study highlights the CSPI’s asymmetric responsiveness to positive and negative macroeconomic shocks, suggesting that investor sentiment and market expectations play a crucial role in shaping stock price reactions. These insights are essential for policymakers in designing macroeconomic policies that foster market stability, as well as for investors in formulating strategies that anticipate market responses to changing economic conditions. Overall, the analysis contributes to a more comprehensive understanding of the dynamic interactions between Indonesia’s stock market and its macroeconomic environment. By demonstrating the usefulness of the ARDL framework, the study provides valuable empirical evidence for academics, policymakers, and market participants seeking to assess and manage risks associated with macroeconomic fluctuations.